The economic cost of preventable disease in Australia: a systematic review of estimates and methods. (7th August 2019) - Crosland, Paul; Ananthapavan, Jaithri; Davison, Jacqueline; Lambert, Michael; Carter, Rob
Abstract: Objective : The aim of this literature review was to establish the economic burden of preventable disease in Australia in terms of attributable health care costs, other costs to government and reduced productivity. Methods : A systematic review was conducted to establish the economic cost of preventable disease in Australia and ascertain the methods used to derive these estimates. Nine databases and the grey literature were searched, limited to the past 10 years, and the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta‐Analysis) guidelines were followed to identify, screen and report on eligible studies. Results : Eighteen studies were included. There were at least three studies examining the attributable costs and economic impact for each risk factor. The greatest costs were related to the productivity impacts of preventable risk factors. Estimates of the annual productivity loss that could be attributed to individual risk factors were between 840 million and 14.9 billion for obesity; up to 10.5 billion due to tobacco; between 1.1 billion and 6.8 billion for excess alcohol consumption; up to 15.6 billion due to physical inactivity and 561 million for individual dietary risk factors. Productivity impacts were included in 15 studies and the human capital approach was the method most often employed (14 studies) to calculate this. Conclusions : Substantial economic burden is caused by lifestyle‐related risk factors. Implications for public health : The significant economic burden associated with preventable disease provides an economic rationale for action to reduce the prevalence of lifestyle‐related risk factors. New analysis of the economic burden of multiple risk factors concurrently is needed.